Lean production in the portuguese textile and clothing industry: The extent of its implementation and role - Maia, Laura Costa (2019)
This chapter aims to explore Lean Production (LP) awareness, the extent of its implementation and role in the Portuguese Textile and Clothing Industry (TCI). For this purpose, a questionnaire, applied in two periods (2011 and 2015), and a set of interviews carried out in 2018 with managers of selected companies, were used for data collection. The study covered a representative sample of TCI companies that accepted the challenge, reflecting the existing pattern and extent of LP implementation and the role within the Portuguese economy. The questionnaire was developed to understand if TCI companies know what LP model is, if implemented, and the evolution over the last years. It was also intended to understand the level of implementation of the LP model in this industry. In 2015, a low percentage of companies had considered implementing LP (approximately 18%). Conversely, the majority of companies considered implementing this model in the near future (approximately 56%). The companies that implemented LP reported difficulties in the implementation and pointed out some measures taken to overcome them. Through face-to-face interviews, the authors wanted to confirm the current condition of LP model implementation and if it was, in fact, implemented, understanding the way how companies have been implementing LP model. The interviewed companies were the ones that responded positively to the 2015 questionnaire. At the same time, it was intended to identify current difficulties and if they were the same as reported in 2015. With these figures, the authors wanted to discourse about current requirements and needs to implement LP in the TCI. Also, attended to the arrival of the Industry 4.0, that facilitates the process optimization, what is the role of LP on this context and to enhance the importance and why companies should implement LP.